CCAFS impact assessment of national policy engagement in Kenya and livelihood impact of uptake of climate-smart agriculture technologies and practices - 2021 - Okumu, Boscow (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The study assessed the impact of CCAFS engagement at policy and household level in Kenya. Specifically, the study assessed the extent to which CCAFS engagement contributed to the observed changes in terms of shaping policy and CSA coordination among others. At the household level the study assessed the factors influencing uptake of CSA practices among smallholder farmers and the subsequent impact of the CSA practices on household dietary diversity, value of household livestock holding and household assets and per capita monthly expenditure as well as GHG emission. The study used a mix of qualitative and quantitative approaches. Specifically, key informant interviews, focus group discussions, observation, and cross-sectional data from household interviews. The study also used econometrics techniques such as the inverse probability weighting regression model, instrumental variable (IV) and Lewbel’s heteroscedasticity based IV approach were used to assess the impact at household level.